The antecedents of organizational resilience: Towards improving the sustainability of public sector organizations in Nigeria - Abdullahi, Usman (2024)
This study explored the impact of antecedents of organizational resilience (organizational agility, crisis anticipation, organizational robustness, organizational adaptability, and organizational learning) on enhancing the sustainability of public sector organizations (PSOs) in Nigeria, drawing on the Dynamic Capabilities Theory. The research collected the data from 306 employees as the PSOs sampled in Kano State, Nigeria, through a cross-sectional approach. Multi-stage cluster sampling was employed to choose the necessary clusters, followed by simple random sampling to select the final samples from the total population. Self-administered questionnaires were distributed and collected. Hypotheses were examined using the Smart-PLS 4 statistical software for partial least squares structural equation modeling (PLS-SEM). The results indicated that organizational agility significantly and positively influenced organizational sustainability. Additionally, the relationship between crisis anticipation, organizational robustness, and organizational learning was also significant and positively related to organizational sustainability. However, organizational adaptability has not significantly and positively influenced organizational sustainability. The study's findings offer crucial insights for leaders, researchers, and policymakers, emphasizing the importance of organizational resilience in enhancing the sustainability of PSOs. The research suggests that to improve the organization's capacity to tolerate shocks from the environment, conceptual and empirical developments are needed to make sense of the effects of organizational resilience and how they might be leveraged into sustainability gains for organizations. The implications of these findings were discussed in terms of theoretical and practical applications.